Preserving the collective. Strategies, challenges and fatigue in coping with individualization and multiple belongings - Busso, Sandro; Garau, Michele (SocietàMutamentoPolitica, 2024)
The process of individualization and the proliferation of multiple memberships have long undermined the classical model of the “synthesis structures” in which the multiple styles of engagement of activists and militants used to be embedded. Even if they do not mark their demise or the tout court disappearance of collective identities, they do impose changes in order to make possible the creation of collective actors (in the most proper sense) capable of embracing an increasing heterogeneity of their members. Within this scenario, the article focuses on how activists who are not resigned to the fact that individualization is an inevitable process attempt to preserve a collective dimension as the core of their political engagement. The need to address loose participation and the presence of multiple affiliations without being able to rely on past solutions implies first bringing the collective into play not as taken for granted, but rather as the stake of strategies that have to be elaborated: not so much a means, but rather increasingly an end of political action. Besides exploring the strategies put in place to achieve this goal, the article focuses on the difficulty and the fatigue of handling this challenge. Such a fatigue will is defined in terms of «active disaffection», to signify as much the disillusionment that even at a young age seems to unify the trajectories of militancy, as the commitment to find alternative paths toward a goal that is considered imperative.